HIV Infection Is Associated with Impaired Striatal Function during Inhibition with Normal Cortical Functioning on Functional MRI. (5th October 2015) - du Plessis, Stéfan; Vink, Matthijs; Joska, John A.; Koutsilieri, Eleni; Bagadia, Asif; Stein, Dan J; Emsley, Robin
Abstract: The aim of the present study was to investigate the effect of HIV infection on cortical and subcortical regions of the frontal-striatal system involved in the inhibition of voluntary movement. Functional MRI (fMRI) studies suggest that human immunodeficiency virus (HIV) infection is associated with frontostriatal dysfunction. While frontostriatal systems play a key role in behavioral inhibition, there are to our knowledge no fMRI studies investigating the potential impact of HIV on systems involved during the inhibition of voluntary movement. A total of 17 combined antiretroviral therapy (cART) naïve HIV+ participants as well as 18 age, gender, ethnic, education matched healthy controls performed a modified version of the stop-signal paradigm. This paradigm assessed behavior as well as functional brain activity associated with motor execution, reactive inhibition (outright stopping) and proactive inhibition (anticipatory response slowing before stopping). HIV+ participants showed significantly slower responses during motor execution compared to healthy controls, whereas they had normal proactive response slowing. Putamen hypoactivation was evident in the HIV+ participants based on successful stopping, indicating subcortical dysfunction during reactive inhibition. HIV+ participants showed normal cortical functioning during proactive inhibition. Our data provide evidence that HIV infection is associated with subcortical dysfunction during reactive inhibition, accompanied by relatively normal higher cortical functioning during proactive inhibition. This suggests that HIV infection may primarily involve basic striatal-mediated control processes in cART naïve participants. ( JINS, 2015, 21, 722–731)